1983
DOI: 10.3109/10408448309128255
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Literature on Carbon Disulfide Toxicity

Abstract: A. Human StudiesInhalation is the major route of occupational exposure to carbon disulfide. Investigations in volunteers and occupationally exposed workers suggest that equilibrium between inhaled and exhaled CS2 is generally attained during the first 2 hr of Initially, the fraction of inhaled CS2 absorbed was relatively constant over a wide range of exposure concentrations, with approximately 70 to 80% of the inhaled carbon disulfide a b s~r b e d .~' .~~~~~~~ At equilibrium, retention of inhaled CS2 declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 300 publications
4
81
0
1
Order By: Relevance
“…This most probably supports the suggestion that CDS only manifests its coronary effect in the presence ofothers predisposing factors (1).…”
Section: Discussionsupporting
confidence: 76%
“…This most probably supports the suggestion that CDS only manifests its coronary effect in the presence ofothers predisposing factors (1).…”
Section: Discussionsupporting
confidence: 76%
“…However, no effect on PDTC toxicity was seen (data not shown), indicating that cytochrome P-450-dependent bioactivation is not involved in the toxic effect of PDTC in our system. DDC can spontaneously decompose to diethylamine and CS 2 , where CS 2 has well documented toxicity (47). This type of reaction does not seem to be crucial in our system since the transport of copper is necessary for PDTC to mediate its toxic action, although the decomposition of PDTC inside cells may facilitate the intracellular release of chelated copper and thereby enhance the potential for oxidative damage to occur.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed report on the toxicity of CS 2 has been published in 1982 [1]. It is shown that CS 2 can enter the human body by inhalation or by permeation through the skin.…”
Section: Discussionmentioning
confidence: 99%